Writing for Justice in First-Year Composition (FYC) - McCoy, Shane A. (Radical Teacher, 2020)
Conceptualized as writing for justice, I offer close-scrutiny and analyses of teaching artifacts that animate my course syllabi in order to understand how first-year composition (FYC) courses might function as a vehicle for advancing social justice. Specifically, this essay offers a framework for enabling students with the critical capacities to transfer social justice knowledge from the classroom to the street. With close readings of my curricula and borrowing from the scholarship on knowledge transfer studies (Bawarshi & Reiff 2011; Beaufort 2007; Yancey 2011), I bridge the theoretical framework of writing for justice to a practice of writing for justice in curriculum design and development. As I argue here, this aspect of the curriculum provides the framework for crafting a FYC curriculum that aims to transform undergraduate students’ cognitive schemas by forming new “impressions” (Ahmed 2004) of social justice.